2004
DOI: 10.1210/jc.2003-032240
|View full text |Cite
|
Sign up to set email alerts
|

11β-Hydroxysteroid Dehydrogenase Type 1 Activity in Lean and Obese Males with Type 2 Diabetes Mellitus

Abstract: Glucocorticoids play an important role in the pathogenesis of obesity and insulin resistance. Impaired conversion of cortisone (E) to cortisol (F) by the type 1 isoenzyme of 11beta-hydroxysteroid dehydrogenase (11beta-HSD) in obesity may represent a protective mechanism preventing ongoing weight gain and glucose intolerance. We have studied glucocorticoid metabolism in 33 male subjects with type 2 diabetes mellitus [age, 44.2 +/- 13 yr; body mass index (BMI), 31.1 +/- 7.5 kg/m(2) (mean +/- sd)] and 38 normal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
1
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(109 citation statements)
references
References 51 publications
7
97
1
4
Order By: Relevance
“…This observation is consistent with the results of previous studies that have suggested that elevated glucose production is not a feature of obesity alone (49), although among diabetic subjects, the increased glucose production rate is exaggerated by obesity (50). A recent study, albeit relying on urinary cortisol-to-cortisone metabolite ratios, has suggested that the downregulation of 11HSD1 in the liver with increasing obesity is less pronounced in type 2 diabetic patients (19). The incremental effect on hepatic insulin sensitivity with carbenoxolone was greater in lean healthy subjects (32) and diabetic patients (33) than we found here in obese patients.…”
Section: Hsd1 In Obesitysupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is consistent with the results of previous studies that have suggested that elevated glucose production is not a feature of obesity alone (49), although among diabetic subjects, the increased glucose production rate is exaggerated by obesity (50). A recent study, albeit relying on urinary cortisol-to-cortisone metabolite ratios, has suggested that the downregulation of 11HSD1 in the liver with increasing obesity is less pronounced in type 2 diabetic patients (19). The incremental effect on hepatic insulin sensitivity with carbenoxolone was greater in lean healthy subjects (32) and diabetic patients (33) than we found here in obese patients.…”
Section: Hsd1 In Obesitysupporting
confidence: 92%
“…The conventional measure of 11HSD1 is the ratio of urinary cortisol to cortisone metabolites, which is inconsistently altered in obesity (11)(12)(13)(14)(15)(16) and diabetes (17)(18)(19). However, this ratio may be confounded by the activity of other enzymes (e.g., 11HSD type 2, 5␣-and 5␤-reductase) that differ in obesity, and is insensitive to the tissue-specific changes in 11HSD1 that have been observed in animals.…”
mentioning
confidence: 99%
“…In the liver no alterations were found in type 2 diabetes whereas a downregulation was found in obese individuals (62). Even though there are many questions to resolve about regulation of 11β-HSD-1, it may be an attractive drug target for future treatments of obesity and diabetes.…”
Section: Page 11 Of 28mentioning
confidence: 98%
“…reduced hepatic glucose output, reduced adipocyte differentiation). Of interest is that a BMI-related reduction in 11 -HSD1 activity is not observed in type 2 diabetes mellitus (Valsamakis et al 2004). Further prospective studies are required to evaluate the consequences of this upon the development of diabetes in obese subjects.…”
Section: -Hsd1 Human Obesity Insulin Resistance and Metabolic Syndromementioning
confidence: 99%